Refractory ventricular tachycardia treated by a second session of stereotactic arrhythmia radioablation. (November 2022) - Herrera Siklody, C.; Pruvot, E.; Pascale, P.; Kinj, R.; Jumeau, R.; Le Bloa, M.; Teres, C.; Domenichini, G.; Porretta, A.P.; Ozsahin, M.; Bourhis, J.; Schiappacasse, L.
Highlights: Arrhythmia radioablation (STAR) is effective in refractory ventricular tachycardia. We report the first cases of successful re-irradiation of arrhythmogenic substrate. No radiation toxicity was observed after the second STAR. Caution is advised as data on early and late toxicities remain scarce. Abstract: Purpose: Stereotactic arrhythmia radioablation (STAR) is an effective treatment for refractory ventricular tachycardia (VT), but recurrences after STAR were recently published. Herein, we report two cases of successful re-irradiation of the arrhythmogenic substrate. Cases: We present two cases of re-irradiation after recurrence of a previously treated VT with radioablation at a dose of 20 Gy. The VT exit was localized on the border zone of the irradiated volume, which responded positively to re-irradiation at follow-up. Conclusion: These two cases show the technical feasibility of re-irradiation to control recurrent VT after a first STAR.